Perched on a Pedestal in a Positive Deviance Profession. Issue 1 (2nd January 2021) - Heckert, Druann; Morooka, Hideki; Heckert, Alex
ABSTRACT: The clergy are a rare occupational group in that they constitute a case of positive deviance when they adhere to their mandates. A positive deviance categorization of a profession makes it such that society expects the clergy to adhere to both the realistic levels of the norms – applied to most people in society – as well as to the idealistic levels of the norm; reserved for the few. They are positively evaluated for doing so. Interviews were conducted with clergy and with the members of clergy families to examine, from a labeling perspective, how clergy define the idealized norms, the impact those norms have, and how they cope. We found that clergy members are exposed to extremely idealized normative expectations for their behavior. They come to expect it and, for the most part, to accept these expectations. They do experience labeling processes, such that they experience negative appraisals and stigma if they do not meet the idealized expectations, even when their rule violations are minor. They report feelings of guilt, shame, and stress. These lived experiences and labeling processes have consequences for their identities as clergy members. Not surprisingly, the primary coping mechanism they reported using was their faith.